ISKID: INOVASI MEDIA PEMBELAJARAN DIGITAL DALAM MENANAMKAN NILAI INFAK DAN SEDEKAH PADA SISWA SEKOLAH DASAR - Dinda Nailatul Syamsudin; Salwa Aulia Fitriani; Silma Maula Ismaini; Ani Nur Aeni (Universitas Islam Raden Rahmat Malang, 2026)
This study aims to create a web-based digital learning platform called ISKID (Charity and Alms for Children), designed to instill the values of charity and almsgiving in elementary school students. The background of this study stems from the continued prevalence of traditional teaching methods in Islamic Religious Education classes, which do not fully meet students’ learning needs in today’s digital age. Therefore, there is a need for innovation in learning media that is interactive, engaging, and aligned with technological advancements. The ISKID platform is designed with various features, such as video animations, learning outcomes (LO), learning objectives (LO), interactive quizzes, and evaluations in the form of integrated pretests and posttests within a single platform. The research approach adopted is Research and Development (R&D), which encompasses the stages of design, development, validation, and limited implementation. The subjects of this study are sixth-grade students in elementary school. Data collection techniques were conducted through tests (pretests and posttests) as well as observations to analyze student responses during the learning process. The research findings indicate that the use of the ISKID media successfully improved students’ understanding of the material on infaq and sadaqah, as evidenced by the increase in posttest scores compared to pretest scores. Additionally, students demonstrated enthusiasm, active participation, and high interest while using the media. Keywords: digital learning media, website, infak and sedekah, elementary school